2021
DOI: 10.1038/s41598-021-00692-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total splenectomy on peripheral lymphocytes and their subsets in patients with hypersplenism associated with cirrhotic portal hypertension

Abstract: To study the impact of total splenectomy (TS) on peripheral lymphocytes and their subsets in patients with hypersplenism associated with cirrhotic portal hypertension (CPH). We studied 102 consecutive patients who received TS from January 2008 to January 2020 due to CPH-related hypersplenism. A similar number of healthy individuals are used as healthy controls (HC). The total lymphocyte counts and their percentages of B lymphocytes, total T lymphocytes (cluster of differentiation (CD)3+) and their subsets (CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A low platelet count < 30 × 10 9 /L would theoretically be assigned a score of 5 based on this scoring system, indicating that surgery is contraindicated. However, the cause of the platelet reduction would need to be considered because restoration of the platelet count to normal would be possible by performing surgery to remove an enlarged spleen [ 47 , 48 ]. Therefore, we did not include platelet reduction in the scoring and grading of coagulation dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A low platelet count < 30 × 10 9 /L would theoretically be assigned a score of 5 based on this scoring system, indicating that surgery is contraindicated. However, the cause of the platelet reduction would need to be considered because restoration of the platelet count to normal would be possible by performing surgery to remove an enlarged spleen [ 47 , 48 ]. Therefore, we did not include platelet reduction in the scoring and grading of coagulation dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al showed that patients with cirrhosis and hypertension have improved PLT counts and aggregation function after laparoscopic SPD compared to those without surgery [ 12 ]. Patients who underwent total splenectomy showed a significant increase in the total lymphocyte count, including B lymphocytes, total T lymphocytes, and their subsets, which improved immune function as a result [ 13 ]. Moreover, splenectomy not only reduces PH but also has positive effects on liver metabolism [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total splenectomy was performed for treatment, and general anesthesia was performed under endotracheal intubation. [ 6 , 7 ]…”
Section: Methodsmentioning
confidence: 99%